Pengaruh Work-Life Balance Dan Time Pressure Terhadap Kinerja Auditor - Anggono, Anggono; Teng, Sauh Hwee; Nasution, Siti Aisyah; Irawan, Ari; Tarwiyah, Tarwiyah (Politeknik Ganesha Medan, 2024)
The problem to be investigated in this research is the declining trend in auditor performance at the HGZ Public Accounting Firm. This research aims to analyze the effect of work-life balance and time pressure on auditor performance at the HGZ Public Accounting Firm. The type of research conducted by researchers is ex post facto. HGZ Public Accounting Firm has 60 auditors in total, and the research sample in this study amounted to 51 auditors who were taken by simple random sampling through a lottery drawing. The data collection technique used to obtain data in this research was used in a questionnaire. The data analysis technique used in this research is multiple linear regression, which consists of outer model analysis for instrument validity and reliability and inner model analysis for testing research hypotheses. The results showed that work-life balance had a positive and significant effect on auditor performance, and time pressure had a positive and significant impact on auditor performance. This study concludes that applying work-life balance and high time pressure will improve auditor performance at the HGZ Public Accounting Firm. The research implication that can be given is that the HGZ Public Accounting firm continues to maintain the time pressure policy because this policy is good and updates the work-life balance policy so that auditor performance increases. Two suggestions can be given to future researchers: use comparative causal research in examining auditor performance and look for homogeneous respondents so that the research results can be widely generalized.